MODIFYING ZIP-ZAP GAME TO LEFORI (LEFT OR RIGHT) GAME FOR TEACHING WRITING IN DESCRIPTIVE TEXT - Dwi Fitrya Ningsih; Adi Yusuf (Journal of Research in Foreign Language Teaching (JRFLT), 2021)
In learning writing a descriptive text, the students should be able to imagine the object then describe it into a sentence. However, they often face difficulties during writing process. They frequently do not know what they are going to write or how to start writing it. In this case, the teacher needs a supporting learning media to make the teaching learning process done more effectively. This research was proposed to modify a game as a medium for the teacher to teach a descriptive text. LEFORI game was a modified game from a Zip-zap game. This game was used by the teacher to help the students in learning writing descriptive text. The game was modified based on the students’ need. The design of this research was Design Based Research as proposed by Akker, et al. (2013). To collect the data, this research used an interview and questionnaire. In addition, the assessment of the game was done by giving questionnaire to get judgment from the teacher. The result showed that LEFORI game was very good and appropriate for overcoming students’ problem in learning writing of descriptive text.